A generic bioanalytical method development strategy and fit-for-purpose qualification to support hERG in vitro sample analysis. (December 2011) - Holme, Paul; Payne, Kirsty; Smith, Sonia; Spence, Mike
Background: The amount of method development and assay validation required to support analysis of solutions from in vitro systems is a consideration of analytical laboratories performing this type of analysis. As there is little information from regulatory bodies as to how much assay development and validation is required, analytical laboratories need to decide on the best approach for this type of work. In this paper, we describe an efficient 'fit-for-purpose'' approach that has been developed to support buffer sample analysis from Safety Pharmacology hERG studies.Results: Method development has been minimized with the aid of compound modeling software and generic HPLC–MS/MS analytical systems. The assay is evaluated prior to sample analysis using simple qualification procedures to support 'one-off'' analyses.Conclusion: The result is an efficient process that allows speedy and confident analysis of in vitro samples to successfully support regulatory hERG in vitro studies without the additional workload of a full validation procedure.